Visuospatial Working Memory Mediates the Relationship Between Executive Functioning and Spatial Ability - Wang, Lu; Bolin, Jocelyn; Lu, Zhenqiu; Carr, Martha (Frontiers in Psychology, 2018)
This study seeks to understand the relationships among EF, VSWM, VWM, and spatial ability (mental rotation) through testing a series of mediation models. It is hypothesized that VSWM completely mediates the relationship between EF and mental rotation. It is hypothesized that VWM does not significantly mediate the relationship between EF and mental rotation. Because some EF tests also have a spatial processing demand, one goal of this study was to investigate whether the mediation relationship changes as a result of the type of test used to measure EF. Covariates age and gender were controlled for in theses analyses. The first hypothesis was partially supported by the finding that when the Tower test, an EF test with a strong spatial processing demand, was used to represent EF, VSWM was found to be a significant mediator. However, when the combined switching and inhibition scores from the Color-Interference Test, an EF test with a low spatial processing demand, was used to represent EF, VSWM no longer significantly mediates the relationship between EF and mental rotation, suggesting that the test effect is real and that future studies investigating the relationship between EF and VSWM need to consider differences in the spatial processing demand inherent in different types of EF tests. The second hypothesis was fully supported in that VWM was not found to be significantly mediating the relationship between EF and mental rotation, regardless of whether the Tower test or the Color-Interference Test was used to measure EF. Another goal of the study was to investigate the relative importance of EF, VSWM, and VWM in predicting mental rotation via dominance analysis. It was found that VSWM is more important than VWM in explaining mental rotation; the Tower test is more important than the Color-Interference Test in explaining mental rotation. This latter finding again suggests that the significant relationship between EF and spatial ability reported in some studies may at least be partially accounted for by the spatial processing demand inherent in some EF tests used in those studies.